Pelatihan Pembuatan Sabun Ekoenzim pada Panti Asuhan Yayasan Kesejahteraan Masyarakat Aceh di Desa Kajhu - Zalmita, Novia; Yulianti, Fitriani; Diah, Husna; Rizki, Mentarina; Jummi, Cut Vita Rajiatul (PESARE: Jurnal Pengabdian Sains dan Rekayasa, 2025)
Indonesia produces 67.8 million tons of waste annually, with 60% being organic. Proper waste management is essential to mitigate health and environmental risks. Eco-Enzyme, discovered by Dr. Rosukon Poompanvong, is an innovative solution made from organic waste, sugar, and water. It serves multiple purposes, such as cleaning and fertilizing. A workshop for the youth at YAKESMA Aceh aims to teach them how to create Eco-Enzyme soap from organic waste, fostering environmental awareness and creating economically valuable products. The results of the workshop have been very beneficial to many parties, successfully educating the youth of Yakesma Orphanage (Yayasan Kesejahteraan Masyarakat Aceh) in utilizing organic waste to create eco-enzyme soap, which has economic value, practicality, and is environmentally friendly. This workshop also had a positive impact on the participants by enhancing their knowledge and skills in turning organic waste into eco-enzyme soap.